Uniqueness of semilinear elliptic inverse problem - Chaochun Qu; Ping Wang (International Journal of Mathematics and Mathematical Sciences)
We consider the uniqueness of the inverse problem for a semilinear elliptic differential equation with Dirichlet condition. The necessary and sufficient condition of unique solution is obtained. We improved the results obtained by Isakov and Sylvester (1994) for the same problem.